2010
DOI: 10.1021/jp911405e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of the Resonance Assisted Hydrogen Bond Based on the Combined Extended Transition State Method and Natural Orbitals for Chemical Valence Scheme

Abstract: We have analyzed hydrogen bonding in a number of species, containing from two to four hydrogen bonds. The examples were chosen in such a way that they would enable us to examine three different hydrogen bonds involving OH-O, NH-O, and NH-N. A common feature of the investigated systems is that they all are expected to exhibit resonance assisted hydrogen bonding (RAHB) in the electronic pi-framework. Our analysis was based on a recently developed method that combines the extended transition state scheme with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 57 publications
7
87
0
Order By: Relevance
“…In previous work, we established theoretically that, for the hydrogen bonds in DNA base pairs, the electrostatic interactions and orbital interactions are of equal importance, and that, indeed, the π electrons provide an additional stabilizing component. This finding was reconfirmed by others . However, our work also showed computationally that the synergetic interplay between the delocalization in the π‐electron system and the donor–acceptor interactions in the σ‐electron system was small, that is, the simultaneous occurrence of the π and σ interactions is only slightly stronger than the sum of each of these interactions occurring individually.…”
Section: Introductionsupporting
confidence: 89%
“…In previous work, we established theoretically that, for the hydrogen bonds in DNA base pairs, the electrostatic interactions and orbital interactions are of equal importance, and that, indeed, the π electrons provide an additional stabilizing component. This finding was reconfirmed by others . However, our work also showed computationally that the synergetic interplay between the delocalization in the π‐electron system and the donor–acceptor interactions in the σ‐electron system was small, that is, the simultaneous occurrence of the π and σ interactions is only slightly stronger than the sum of each of these interactions occurring individually.…”
Section: Introductionsupporting
confidence: 89%
“…This picture is further enriched by providing the energetic contributions (Δ E i ) to the bond energy within ETS-NOCV scheme [39]. It has been shown that NOCV’s lead to a compact description of not only metal–ligand or covalent connections [36, 37, 39], but also of hydrogen bonding [40]. We have verified recently the applicability of ETS-NOCV scheme in a description of halogen bonding, showing in particular, that the dominating contribution to the deformation density exhibits the negative-value area that corresponds to σ-hole [41].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the electron transfer chain between two heme rings in cytochrome b 561 is clarified as serials of RAHBs16. However, some other works attribute the cooperativity to long-range electrostatic interactions17, van der Waals interaction18, σ- orbital interaction19, electronic σ- framework rearrangement20 or charge interaction21. Unfortunately, there has been no experimental evidences reported on RAHB in proteins and protein analogs, to the best of our knowledge.…”
mentioning
confidence: 99%